Identifying the major constraints to investment in residential rental property in South Africa - Frew, Marc Alexander (Department of Construction Economics and Management, 2017)
Purpose: This research investigated the constraints to investment in residential rental property in South Africa. This research does not attempt to value or place these constraints in any hierarchical order; rather, it identifies the constraints in the South African context for research in the future. Design: A literature review was conducted, and constraints to residential rental property were identified. A semi-structured interview was then designed, and a field study was launched, interviewing key residential investment property market stakeholders regarding their views on the constraints to investment in residential rental property in South Africa. Quantitative data was used to corroborate the findings of the interviews, and pattern analysis was the technique drawn on to explain the findings. Findings: Participants identified six major constraints to investment in residential rental property in South Africa. These include financial liquidity or funding; property liquidity; management skills; management costs; the lack of investment market information; and legal constraints. Practical Implications: The results of this research will enable further research into the specific constraints mentioned above, in order to assess if there are ways to minimise those constraints going forward.